MENINGKATKAN EFISIENSI ORGANISASI: PERAN KLASIFIKASI BIAYA DALAM PENGAMBILAN KEPUTUSAN - Zakia Fikra; Naila Ariqah Putri; Widya Arsani Malau; Muhammad Rafianda; Mariana Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
This study explores the role of cost classification in improving organizational efficiency and its impact on decision-making processes. The primary objective is to analyze how accurate cost classification aids managers in understanding fixed, variable, direct, and indirect costs to make more informed financial decisions. By employing effective cost control and budget planning strategies, organizations can better manage their resources, reduce unnecessary expenditures, and improve overall performance. This research utilizes a case study approach to highlight practical examples of how cost classification directly contributes to operational efficiency. The findings indicate that proper cost classification not only facilitates decision-making but also enhances competitiveness in a highly dynamic market. Recommendations are provided to help organizations integrate cost classification into their financial management systems for sustainable growth.